The exact solutions with generalized separation of variables of the nonlinear heat equation - Barannyk, A. F.; Barannyk, Т. А.; Yuryk, I. I. (Ukrains’kyi Matematychnyi Zhurnal, 2022)
UDC 517.9We propose a method for construction of exact solutions to nonlinear heat equation which is based on the classic method of separating variables, its generalization, and Lie reduction method. Substitutions that reduce the nonlinear heat equation to ordinary differential equations are considered and the classes of exact solutions by means of the generalized separation of variables method are constructed.